Integrasi Nilai Tawakal dalam Al-Qur’an sebagai Metode Penguatan Diri bagi Penderita Insecure: Studi Maudhu’i - Firdatul Maslachah, Ana; Hakam Chozin, Fadjrul (AT-TAISIR: Journal of Indonesian Tafsir Studies, 2024)
Insecurity, characterized by fear, worry, or anxiety about the future or past events, can be managed with or without external support, including trusting in Allah. This study delves into three key questions, how do Quranic verses about trust (tawakal) aid individuals in independently handling insecurity?, what interpretations exist regarding these verses and their relevance to managing insecurity independently?, how do Quranic verses on tawakal offer solutions to insecurity?. Conducted through library research using a thematic method, the study gathers verses from various surahs addressing similar themes. Findings reveal verses related to self-management of insecurity, such as concern for the future (At-Taubah: 51, Ali 'Imran: 159, At-Thalaq: 2-3), family overprotectiveness (An-Nisa: 81), fear and anxiety (Al-Maidah: 23), past trauma (Al-Anfal: 2), and rejection (An-Nahl: 99). Commentators argue against excessive worry about the future or sustenance, advocating reliance on Allah's guidance through life's challenges. Thus, the Quran offers guidance and reassurance for individuals grappling with insecurity, emphasizing trust in a higher power as a means of finding peace and resilience.